Health and Wellbeing of Sexual Minorities [Medidas de Salud Mental y Bienestar Subjetivo en Una Muestra de Hombres Gays y Mujeres Lesbianas en Chile] - Barrientos-Delgado, J (Sociedad Medica de Santiago, 2017)
Background: Most of the information in Chile about health and wellbeing of sexual minorities refers to risk behaviors. Aim: To assess health and wellbeing in a sample of Chilean homosexual men and women. Material and Methods: Spanish versions of the Satisfaction With Life Scale and Outcome Questionnaire-45 (OQ-45) were answered by 191 homosexual women and 256 homosexual men aged 18 to 67 years, from four Chilean cities. Results: Lesbian women have better levels of satisfaction with life and adjustment in personal relationships than homosexual men. Eight percent of respondents had suicidal thoughts in some moment of their life. Conclusions: The information gathered in this work could help in the development of mental health policies for sexual minorities. © 2017, Sociedad Medica de Santiago. All rights reserved.